Implementation challenges of merdeka curriculum in primary schools - Yunitasari, Dukha; Suastra, I Wayan; Lasmawan, I Wayan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The aim of this study is to explain the implementation challenges of merdeka curriculum in primary school. The 47 articles were identified to discuss the understanding of merdeka curriculum, to know the merdeka curriculum challenges, and to overcome the challenges. The implementation of the Merdeka Curriculum in Indonesian primary schools presents a number of obstacles, including teacher comprehension of the curriculum, habituation, quality of education, implementation of specific subjects, and teacher preparedness. To ensure a correct understanding of the curriculum and the formation of appropriate habits in teachers, institutions, and students, policymakers should establish effective communication with teachers. Teacher preparation programs that emphasize differentiated learning can prepare educators to implement the Merdeka Curriculum. Integrating values-based learning programs and employing a well-structured educational management flow can also enhance the character education component and optimize the curriculum implementation. In addition, workshops and readiness-raising initiatives can improve teachers' mental and intellectual preparedness for the new curriculum's changes and challenges. By addressing these obstacles, the implementation of the Merdeka Curriculum in Indonesian primary schools can be made more effective, thereby augmenting the quality of education offered to Indonesian students.